Anaerobic digestion of food waste: A review focusing on process stability - Li, Lei; Peng, Xuya; Wang, Xiaoming; Wu, Di (Bioresource technology, 2018)
•AD is a well-established technology for FW management.•Performance instability is a common operational issue for AD of FW.•Methods for improving the stability of anaerobic digesters are reviewed.•Process monitoring and control are suitable for evaluating digester operation.•Microbial management facilitates early diagnosis and optimization of digesters. Food waste (FW) is rich in biomass energy, and increasing numbers of national programs are being established to recover energy from FW using anaerobic digestion (AD). However process instability is a common operational issue for AD of FW. Process monitoring and control as well as microbial management can be used to control instability and increase the energy conversion efficiency of anaerobic digesters. Here, we review research progress related to these methods and identify existing limitations to efficient AD; recommendations for future research are also discussed. Process monitoring and control are suitable for evaluating the current operational status of digesters, whereas microbial management can facilitate early diagnosis and process optimization. Optimizing and combining these two methods are necessary to improve AD efficiency.